ASSOCIATION OF MATERNAL HYPERTENSION WITH PLACENTAL ABRUPTION - Khattak, Samina Naseem; Deeba, Farhat; Ayaz, Attiya; Khattak, Muhammad Irfan (Journal of Ayub Medical College Abbottabad, 2012)
Background: Placental abruption is one of the leading causes of maternal mortality and morbidity. Many causes predispose an expecting mother to placental abruption, such as trauma, previous history, smoking, ethnicity and hypertension. The present study concentrated on maternal hypertension as a cause of abruption. Methods: All subjects of this comparative study underwent a complete obstetrical clinical workup comprising history, general physical examination, abdominal and pelvic examination, and relevant investigations. The maternal condition was assessed and managed according to established labour ward protocols, which included both pharmacological and surgical intervention. Patients were allotted various subgroups for detailed data analysis and comparative analysis. Results: A total of 50 cases and 50 controls for placental abruption were studied during the study period. Both groups were compared based on parity, gestational age, proteinurea, haemoglobin, and hypertension. Mean systolic blood pressure (SBP) of cases in this study was 155±7.8 mmHg versus mean SBP for controls was 120±14 mmHg. Mean diastolic blood pressure (DBP) of the cases was 104±6.6 mmHg compared to controls where mean DBP was 71±11 mmHg. Among the controls, 45 (90%) had blood pressures in the normal range. There was statistically significant differences between cases and controls with respect to hypertension (p<0.01). Conclusion: Placental abruption is strongly associated with maternal hypertension. Keywords: Placental Abruption, Hypertension, Maternal Morbidity, Antepartum Haemorrhage (APH)